Bi-hierarchical porous Pt microspheres grown on Ti wire with TiO2 nanotubes layer for selective alcohol sensing. (17th March 2022) - Fedorov, Fedor S; Goldt, Anastasia E; Zamansky, Konstantin; Vasilkov, Mikhail Yu; Gaev, Andrey; Lantsberg, Anna V; Zaytsev, Valeriy; Aslyamov, Timur; Nasibulin, Albert G
Abstract : A smart one-electrode sensor is designed for selective alcohol detection. Decoration of titania nanotubes grown on the surface of Ti-wire by Pt microspheres yields improved sensitivity towards low-molecular weight alcohols. While thermal cycling operation of this one-electrode sensor only ensures discrimination of alcohol homologs with a help of a machine learning routine. ABSTRACT: This study focuses on the synthesis of bi-hierarchical porous Pt microspheres directly on titania nanotube arrays grown on a Ti wire for their application as a one-electrode selective alcohol sensor. We evaluate the synthesis conditions, morphology, structure of the obtained material using scanning, transmission electron microscopy and electron diffraction. The sensor performance is assessed in a one-electrode configuration, using thermocycling protocols both to heat and acquire a signal that we further process with a machine learning algorithm for selective determination of alcohols. We found that reduction of Pt precursor by formic acid facilitates the appearance of quasi-1D Pt structures without using any surfactant. High excess of formic acid yields the formation of quasi-dendritic Pt structures with the overall morphology of a sphere and channels whose diameter remains one of the TiO2 nanotubes. Our data suggest the growth of Pt spheres to be diffusion controlled with constant or decreasing nucleation rate that should include assembling of Pt nanorods. The fabricated sensors based on the synthesized structures show a chemiresistive response to methanol, ethanol and isopropanol vapors in the mixture with air, which we selectively determine using only one sensor. Graphical Abstract: